Identification of inhibitors against the potential ligandable sites in the active cholera toxin. (April 2015) - Gangopadhyay, Aditi; Datta, Abhijit
Graphical abstract: Highlights: Identification of ligandable sites in A1–ARF6 active cholera toxin using computational solvent mapping and probe binding approaches. Two potential ligandable sites identified at A1–ARF6 interface and A1 active site. Based on probe binding affinity, docking based virtual screening performed against ligandable sites. Interface inhibitors include phosphates, guanidines, Pteridine. Phosphates and indoles identified as A1 active site inhibitors. Abstract: The active cholera toxin responsible for the massive loss of water and ions in cholera patients via its ADP ribosylation activity is a heterodimer of the A1 subunit of the bacterial holotoxin and the human cytosolic ARF6 (ADP Ribosylation Factor 6). The active toxin is a potential target for the design of inhibitors against cholera. In this study we identified the potential ligandable sites of the active cholera toxin which can serve as binding sites for drug-like molecules. By employing an energy-based approach to identify ligand binding sites, and comparison with the results of computational solvent mapping, we identified two potential ligandable sites in the active toxin which can be targeted during structure-based drug design against cholera. Based on the probe affinities of the identified ligandable regions, docking-based virtual screening was employed to identify probable inhibitors against these sites. Several indole-based alkaloids and phosphates showed strong interactions to the important residues of the ligandable region at the A1 active site. On the other hand, 26 top scoring hits were identified against the ligandable region at the A1 ARF6 interface which showed strong hydrogen bonding interactions, including guanidines, phosphates, Leucopterin and Aristolochic acid VIa. This study has important implications in the application of hybrid structure-based and ligand-based methods against the identified ligandable sites using the identified inhibitors as reference ligands, for drug design against the active cholera toxin.